La actividad minera y el lugar que ocupa en la economía mexicana del siglo xix - Inés Herrera; Alma Parra (Caravelle)
Mineral wealth has represented for many centuries the basis of Mexican economy’s external sector. During the 19th century the exploitation of precious minerals as well as industrial ones, has marked national economy and linked the country to those vicissitudes that these products have registered in the international markets, and now upon new political and administrative structures.